Effects of socio-economic factors on agricultural land use in Malaysia. - Olaniyi, Akeem Olawale; Abdullah, Ahmad Makmom; Ramli, Mohammad Firuz; Mohd Sood, Alias (2011)
A study is conducted to investigate the effects of socio economic factors on agricultural land use in Malaysia. Relevant socio – economic variables for the study were aggregated from the databases of various international and national agencies such as FAO, Index Mundi and Malaysian Departments of Agriculture and Statistics. These data were subjected to statistical analysis using stepwise regression method in SPSS versi on 18. Findings indicated that, relevant socio – economic factors in agricultural land use i n Malaysia are available workforce in the population and their working conditions in the agricultural and non – agricultural sectors. This study has revealed that labour supply and their conditions of service are major factors in agricultural land use in Malaysia. This study further underscores the need for greater application labour saving technology in agricultural practices given the competition between agricultural and non – agricultural uses of available workforce in the population.